THE EFFECT OF JOB EVALUATION ON JOB SATISFACTION IN THE MERANGIN TOURISM, YOUTH AND SPORTS DEPARTMENT - Sarinah, Sarinah; Mardalena (Dinasti International Journal of Digital Business Management, 2020)
This research was to find out the effect of Job Evaluation on Job Satisfaction in the Merangin Tourism, Youth and Sports Department (DISPORA), as well as to find out the Effect of Job Evaluation on Job Satisfaction in the Merangin Tourism, Youth and Sports Department (DISPORA). The population in this study were employees at the Merangin Tourism, Youth and Sports Department (DISPORA), 90 respondents and using the Sugiyono formula in determining the number of samples. The research method used in this research is quantitative descriptive research, data collection techniques in this study using questionnaires or questionnaires. Data obtained from the questionnaire were then analyzed using the help of statistical formulas and the help of Microsoft Excel with the validity test method, reliability test, correlation coefficient, coefficient of determination, and hypothesis testing. There is a strong and significant positive influence between work assessment (x) on job satisfaction (y), namely the value of the correlation coefficient (r) = 4.5% The amount of contribution or influence of work assessment (x) on employee performance (y) of 0.212 or close to 1 meaning there is a rather strong relationship between R-Square indicating a large contribution of 0.045. Thus the hypothesis in this study is that there is a positive and significant effect between work assessment of employee performance in the Merangin Tourism, Youth and Sports Department (DISPORA).